MANAGEMENT OF QURAN TRANSLATION LEARNING AT SCHOOLS FOR PROSPECTIVE PREACHERS AT THE ELEMENTARY SCHOOL/MADRASAH IBTIDAIYAH LEVEL AT AL MUSLIMUN JEMBER HOMESCHOOLING - Ahmad Nur Mahfuda; Dimas Herliandis Shodiqin (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
Al-Quran Translation Learning Management for Elementary School Prospective Da'i Level at Al Muslimun Jember Homeschooling is a training process for Prospective Da'i Schools that has a role, a special system method and training that is delivered as well as possible by Prospective Da'i participants. The process of learning Qur'an translation training certainly cannot be separated from the context of the scope of culture that it has. The Al Muslimun Jember Homeschooling Prospective Da'i School Training Institute provides a Qur'an translation learning training program as a basic understanding of Islam both at Elementary (SD/MI) and Middle School (SMP/SMA) levels, namely in the form of the Al-Quran Translation Learning Method for the Meaning of Words, Development of Al-Quran translation learning by pronouncing each word (Lafzhiah) and the Qur'an translation learning module per word (Lafzhiah) per letter. This institution has a big role in facilitating the learning of Al-Quran translation at Al Muslimun Homeschooling. All of them require management, namely the Management of Qur'an translation learning systematically, clearly and correctly directed. Research methodology in the process of collecting and analyzing the necessary data, in order to answer the problems investigated. In the compilation using a descriptive qualitative research method with direct observation in the field. Then describe systematically, factually and accurately. Data sources use primary data and secondary data. Primary data field data, namely the results of interviews and observations. and Secondary data in the form of documents from brochures, magazines and other information materials that are relevant to the research problem as research support. Al Muslimun Homeschooling Education is a fairly effective system in the process of learning Qur'an translation both at the basic level at the SD/ MI level which is done at home. or intermediate level at junior high and high school levels in the process of learning advanced Qur'an translation. In addition, homeschooling learning can be done anywhere other than at school, such as in mosques, in markets, in rice fields, in forests, and in other places that can be sources of learning.